Implications of anomalous gauge boson interactions to the fermion electromagnetic moments - Bento, Luis (2017)
We calculate the electromagnetic fermion form-factors induced by the anomalous gauge boson interactions contained in the operators ODW and ODB. Other results regarding anomalous triple gauge boson interactions are briefly overviewed. We study the interplay between vertex corrections and gauge boson self-energies extended to the longitudinal degrees of freedom. The physical couplings to an external electromagnetic field are then derived.